Sequencing of Jobs and Time Optimization for Fly-ash Brick Production - Avijit Bhowmick, Arup Kumar Nandi, Goutam Sutradhar (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
To control overall duration, the research used a model based on an algorithm for work scheduling. The association status among tasks arrangement and time of delivery was explored, as was its significant effect on total elapsed time management. Using a survey study design, data were gathered via in-depth observations and interviews of pre- and post-production processes within the chosen fly-ash brick industry. The results demonstrated that the work sequencing model significantly affects total expire time management. The results also showed that the buffer stock could be increased and improved in case of unforeseen future demand, cycle time could be reduced, and the delivery date to the client could be moved forward. The time saved may seem like a freebie, but it will really increase the company's bottom line. Companies should make an effort to use task sequencing model methods throughout their operations and cultivate a culture of teamwork aimed at reducing expenses wherever possible.